UPAYA MENUMBUHKAN MINAT BACA ANAK MELALUI PERMAINAN ABACA FLASH CARD DI RA AISYIAH KECAMATAN KRUI SELATAN KABUPATEN PESISIR BARAT - Nuryanti, Eva; Mazdayani, Mazdayani (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2020)
This study aims to increase children's reading interest through abaca flashcard games for students at the Raudhatul Athfal (RA) level. The subjects in this study were students of group B with a total of 20 students, consisting of 6 female students and 14 male students. The research was carried out in March-April 2020 at RA Aisyiah Pekon Letakan in group B students. The object of this study is a beginner's reading interest which includes pleasure, interest, initiative, and attention to the abaca flashcard game. The research instrument used observation sheets and documentation. The data analysis technique used quantitative descriptive with percentage technique. The results showed that the beginner reading interest in group B children at RA Aisyiah Letakan could be increased through playing abaca flash cards.